CREATION OF ETHNOGRAPHIES WITH POPULAR TRADITIONS - Eshmurodova Zarifa Rakhmonberdiyevna (International Engineering Journal For Research & Development, 2020)
The article discusses in detail the national customs and traditions of our ancestors, which perfectly reflect the lifestyle, dreams, aspirations, customs and rituels, traditions and Uzbek sincerity. The influence of various factors in the formation of etnographies associated with the still forgotten folk traditions, the avoidance of various harmful influences today, the ancient national tradition in any case, the ancient tradition of our people to have unique qualities and the importance of living by and adhering to our values.